2021
DOI: 10.2459/jcm.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of QRS duration on left ventricular remodelling and survival in patients with heart failure

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Neither sacubitril/valsartan nor sodium–glucose cotransporter inhibitors were available when these trials of CRT‐P were being conducted. However, it is likely that the benefits of CRT‐P and these newer interventions are complementary 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither sacubitril/valsartan nor sodium–glucose cotransporter inhibitors were available when these trials of CRT‐P were being conducted. However, it is likely that the benefits of CRT‐P and these newer interventions are complementary 28 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that the benefits of CRT-P and these newer interventions are complementary. 28 Some analyses suggest that women obtain more benefit from CRT than men. 29 We did not find this.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our data are in line with previous observations that linked NTproBNP levels > 1000 pg/ml to progressive LV remodelling[ 20 ] and reflect to those of Xiao et al which demonstrated that in patients with dilated cardiomyopathy QRS width progression is independent of medical therapy[ 15 ]. Critically, the rapid progression of remodelling and worse prognosis seen in people with broad QRS, the lack of reverse remodelling in response to optimal therapy in this group in the absence of CRT[ 3 ], and the solid evidence of beneficial remodelling apparent following CRT[ 21 ] underlines a close link between the QRS duration and LV remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the age-adjusted incidence is falling, the background of an aging population means the overall incidence is increasing [ 2 ]. QRS complex prolongation, particularly left bundle branch block > 120 ms, is an established prognostic marker in patients with heart failure due to reduced ejection fraction (HFrEF), and is independently associated with worsening symptoms, progressive remodelling less amenable to medical therapy [ 3 ], hospitalisation and all-cause mortality [ 4 , 5 ]. For these patients, cardiac resynchronisation therapy (CRT) in combination with medical therapy can halt clinical progression and induce reverse remodelling, thereby improving symptoms and prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible compromise, especially for patients with new HFrEF as a consequence of myocardial infarction, wearable cardioverter-defibrillators may be considered although these have not been proven to reduce the risk of morality and carry a risk of inappropriate shocks [ 51 ]. On the other hand, for those patients with an indication for CRT who are at high-risk of sudden cardiac death, and might otherwise be considered for an ICD, deferring treatment may be disadvantageous, especially considering that a broad QRS (especially left bundle branch block) is a consistent predictor of worse outcomes and failure to remodel in response to medical therapy [ 52 ], and so inpatient implantation of a CRT-defibrillator might be considered reasonable in selected patients.…”
Section: How To Modify Prognosis For the Hospitalised Patientmentioning
confidence: 99%